SPEAKING IN PROCEDURE TEXT BY RETELLING USING PICTURE SERIES - Tis’ah, J. Anhar Rabi Hamsah; Usadiati, Wahjuningsih; Luardini, Maria Arina (Program Studi Magister Pendidikan Bahasa Inggris, Program Pascasarjana, Universitas Palangka Raya, 2019)
The main objective of the research was to know the effect of speaking of procedure text by retelling using picture series on students’ speaking achievement of MTs Miftahul Jannah Palangka Raya. Quasi-experimental research was done in randomized control group pre-test post-test design to the answer of the research problem. The population was the students of grade 7 of MTs Miftahul Jannah Palangka Raya, and the samples of grades 7A and 7B were taken randomly from the population to be the control and exerimental groups. The data were obtained from the scores of speaking taken from the samples of the research. To test the hypothesis of the research, statistical calculation was done using t-test. Based on the result of hypothesis test calculation, it was found that the value of tobserved was greater than the value of ttable. i.e. 20.019 > 1.671 that Ha was accepted and H0 was rejected. It means picture series gave effect on the speaking achievement of retelling of students of MTs Miftahul Jannah Palangka Raya.